Consumption during the Great Recession in Italy - Martina Celidoni; Michele De Nadai; Guglielmo Weber (Institute for Fiscal Studies (IFS), 2016)
We use Italian micro data to investigate how consumers reacted to the Great Recession. In particular, we study the age profiles of non-durable consumption, durable purchases and wealth over the 2008-2012 period for different year-of-birth cohorts, and how they departed from the way they would have been had consumer behavior been the same as it was over the 1995-2006 period. We find that consumption dropped most for younger households - only part of these drops can be explained by the increase in unemployment. We also investigate whether the crisis had an impact on the way consumers allocate their spending among broad consumption bundles. We find that the budget elasticity of the demand for food changed during the recession period, particularly among the young.
Keywords: 330